"Some guidance and somewhere safe": Caregiver and clinician perspectives on service provision for families of young people experiencing serious suicide ideation and attempt. (11th September 2018) - Dempsey, Sarah‐Jane A.; Halperin, Steve; Smith, Karen; Davey, Christopher G.; McKechnie, Ben; Edwards, Jane; Rice, Simon M.
Abstract: Background: Previous research has recommended the involvement of caregivers in the treatment of young people with depressive illness, but the best form and type of involvement remains largely unknown. This qualitative study aimed to explore clinician and caregiver perspectives on service provision for family members of young people (15–25 years) attending a specialist clinic for moderate–severe mood disorder. Methods: Eight caregivers, and eight specialist clinicians were interviewed via a semi‐structured interview. Thematic analysis was used to interpret qualitative findings. Results: Thematic analysis revealed four key themes related to caregivers initial needs, crisis needs, discharge needs and broad challenges. Recurrent subthemes included the need for both information and support, especially at times of heightened suicide risk, or preceding a suicide attempt. Caregivers sought greater information, specific to their young person, and more support and guidance in their role managing the safety of the young person in their care. Conclusions: Results highlight that addressing the unmet support and information needs of caregivers may be of benefit to all (both the caregivers and the young person in their care). The lived experience of caregivers in this study indicates the significant stressors placed on them (especially when the young person they are supporting is at high risk of suicide), and the need to develop efficient and cost‐effective ways to enhance their perceived competence and skills. Implications are discussed for practitioners working with young people experiencing ongoing suicidal ideation.